Effects of increasing narasin doses on feedlot performance, feeding behavior, carcass traits, and rumen-cecum morphometrics in Nellore cattle - Leandro Aparecido Ferreira da Silva; Daniel Moretto Casali; Ana Laura Januário Lelis; Tiago Leiva; Murilo Chuba Rodrigues; José Paulo Roman Barroso; Pedro Veloso Facury Lasmar; Giovanna Lombardi de Oliveira Araújo; Gercino Ferreira Virgínio Júnior; Johnny Maciel de Souza; Danilo Domingues Millen (PLoS ONE, 2026)
Narasin is an ionophore commonly used to improve energy efficiency and feed utilization in beef cattle. This study evaluated the impact of increasing levels of narasin on performance, feeding behavior, carcass traits, and ruminal and cecum morphometrics of Nellore cattle in feedlot. One hundred twenty-eight Nellore yearling bulls (393 ± 24 kg) were blocked by initial body weight (BW), allocated in 32 pens (4 bulls/pen). Pens were randomly assigned to one of four treatments: 0 (control), 13, 20, or 27 ppm of narasin. After a 14-day adaptation, animals were fed a high-concentrate diet (87% concentrate, dry matter basis) for 98 days. Narasin was not included in the diet from day 109 to day 111 due to the withdrawal period required by the active compound. Animals were slaughtered on day 112. A significant linear effect of narasin was observed on BW (P = 0.02) and average daily gain (P = 0.01) during the first 28 days, with improved feed efficiency at 20-ppm (P = 0.03). These effects did not persist over the full 111 d period. Cattle receiving 20-ppm of narasin had longer meal durations on day 70 (P = 0.05). A quadratic effect was observed on the thickness of fat at the 12th rib (P = 0.05), with the highest mean value observed at 20 ppm. The 13-ppm level increased the rumen papillae size (P = 0.02), while higher levels reduced the number of goblet cells in the cecum (P = 0.01). Narasin supplementation enhanced early feedlot performance and carcass fat deposition without negatively affecting dry matter intake. Narasin can be used in feedlot diets from 13 to 27 ppm, with 20 ppm being the most effective level for improving performance and carcass quality.